ANALISIS HAMBATAN GURU DALAM PEMANFAATAN AI SEBAGAI MEDIA PEMBELAJARAN DI SDN TENGKI 01 - Fauziana, Azmi; Baedowi, Sunan; Wakhyudin, Husni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of Artificial Intelligence (AI) has encouraged its implementation in education, including elementary schools. However, AI utilization in learning has not been optimally implemented due to various obstacles experienced by teachers. This study aims to analyze teachers' barriers in utilizing AI as a learning medium, identify the factors causing these barriers, and describe teachers' efforts to overcome them at SD Negeri Tengki 01. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving one principal and twelve teachers. The data were analyzed using the Miles, Huberman, and Saldana interactive analysis model. The findings revealed that teachers experienced internal barriers, including limited understanding of AI, inadequate digital competencies, and dependence on conventional teaching methods. External barriers consisted of limited technological facilities, inadequate internet access, and the absence of AI-related professional development programs. Psychological barriers were also identified, including low self-confidence and anxiety in adopting new technologies. Teachers attempted to overcome these challenges through self- directed learning, participation in webinars, discussions with colleagues, and involvement in Teacher Working Group (KKG) activities. The study concludes that AI implementation as a learning medium at SD Negeri Tengki 01 has not yet been optimal due to the interaction of internal, external, and psychological barriers. Therefore, schools should strengthen technological infrastructure and provide sustainable professional development programs to improve teachers' digital competencies.